Memory Fusion Sampled-Data Control of Fractional-Order Heterogeneous Multiagent Systems Subject to DoS Attacks and Time Delays: A Resilient Binary Sampled-Data Scheme - Chen, Yiwen; Merzouki, Rochdi; Jiang, Jun; Defoort, Michael; Djemai, Mohamed (IEEE transactions on cybernetics, 2025)
Sampled-data control of heterogeneous fractional-order (FO) multiagent systems (MASs) under nonidentical denial-of-service (DoS) attacks and time delays is investigated in this study. Based on the received acknowledgments, the designed channel-dependent resilient binary sampled-data scheme adjusts the sampling period following two geometric progressions in the absence and presence of DoS attacks. This provides finer adjustments in sampling periods and ensures a lower average sampling rate compared with traditional periodic sampling schemes. Moreover, the upper and lower bounds of sampling intervals in different channels are heterogeneous, in which only the lower bounds are constrained by inequalities associated with the coefficients of DoS attacks. The impact of DoS attacks is observed from the viewpoint of the overall communication network topology. Observation of the joint recovery time series, defined as those time instants that the joint union of the sampling-based communication graphs under asynchronous DoS attacks can recover to the original topology graph, measures the effectiveness of the designed sampling scheme in restoring the connectivity of communication network under DoS attacks. Heterogeneous memory fusion controllers are used to achieve consensus of FO MASs with time delays based on the distributed asynchronous gradient algorithm. An example is presented to illustrative the validity of the theoretical analysis.